2008
DOI: 10.2139/ssrn.1136816
|View full text |Cite
|
Sign up to set email alerts
|

Business Constraints and Growth Potential of Micro and Small Manufacturing Enterprises in Uganda

Abstract: Ugandan micro-and small enterprises (MSEs) still perform poorly. The paper utilizes data collected in Uganda in March and April 2003 to analyze the business constraints faced by these MSEs. Using a stratified random sampling, a sample of 265MSEs were interviewed. The study focuses on the 105 manufacturing firms that responded to all questions. It examines the extent to which the growth of MSEs is associated with business constraints, while also controlling for owners' attributes and firms' characteristics. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 39 publications
2
15
0
Order By: Relevance
“…However, SMEs in this cluster did not develop competencies in key areas of budgeting, planning of business activities and managing limited finances. According to Ishengoma and Kappel (2008), efficient financial management is a major predictor of profitability and overall performance trends of SMEs.…”
Section: Clustermentioning
confidence: 99%
“…However, SMEs in this cluster did not develop competencies in key areas of budgeting, planning of business activities and managing limited finances. According to Ishengoma and Kappel (2008), efficient financial management is a major predictor of profitability and overall performance trends of SMEs.…”
Section: Clustermentioning
confidence: 99%
“…Ishengoma and Kappel (2008) point out that SMEs' growth potential in rural areas is negatively affected by lack of financial support. Literature indicates that in the rural areas, service infrastructure and business environment have not yet been well developed, and face problems such as the inaccessibility of financial institutions (Liedholm and Mead, 1999), and the inability to get the necessary financing to support their businesses (Romanian Commercial Bank, 2008).…”
Section: Finance Factorsmentioning
confidence: 99%
“…However, SME development and business creation is constrained by poor access to finance (Rogerson, 2008;Okpukpara, 2009), lack of education in entrepreneurship, business skills and leadership (Fieldsend and Nagy, 2006;Rogerson, 2008), lack of marketing knowledge (Lekhanya and Mason, 2013), inflexible regulations (Rogerson, 2008), and lack of access to business resources, high taxes and poor market access (Ishengoma and Kappel, 2008). Fatoki and Garwe (2010) identified internal factors (access to finance, management skills, networking, investment information technology and cost of product) and external factors (economic environment, markets, infrastructure, crime, corruption and labour) that can impact on a business and cause obstacles to growth for new SMEs.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in both Africa and Latin America show that young MSEs are more likely to show high rates of growth compared with MSEs that have been in existence longer [3]. A study revealed that the major expansion of dynamic enterprises occurs during their third year of operation [2], and numerous other studies have shown that the average growth rate of firms decreases with age [4].…”
Section: Firm Age and Its Influence On Growthmentioning
confidence: 99%
“…They produce largely for the low income group and employ lower levels of techniques. Many of them are self-employed type with a low transformation rate into higher size categories and their innovative activities are limited [2].…”
Section: Introductionmentioning
confidence: 99%